(untitled) (Bioresearch Communications, 2024)
The potentiality of citric acid on economy is high because of its multi-purpose uses, particularly in the food and pharmaceutical industries. Bangladesh spent more than one million US dollars to import citric acid mostly from India and China. Its consumption is increasing 3.5–4%, annually, indicating the need for better manufacturing alternatives. Globally, citric acid is primarily produced through microbial fermentation with Aspergillus niger. To support the massive scale of production of citrate, the manufacturing process must be eco-friendly which should be inexpensive and available raw materials for maintaining high yielding in a cost-effective manner. In Bangladesh prospective, the current study has undertaken to optimize citric acid production using one of the most abundant raw materials sugarcane molasses. Moreover, the aim of this study was to determine the optimum conditions to produce citric acid from sugarcane molasses using Aspergillus niger (F-81) by submerged fermentation. The amount of citric acid production was determined by the Marier-Boulet colorimetric method. The optimization data suggested that 10% substrate (from processed cane molasses), 4% inoculum size of A. niger, and initial pH 6.0 allowed to produce around 25.8 g/L citric acid. Further study is warranted to assess the feasibility of citrate production in an industrial level as well as improvement of microbial strains is needed to further enhance citric acid production. Bioresearch Commu. 11(1): 1643-1650, 2025 (January)